The Role of Green Accounting in Efforts to Prevent Environmental Pollution to Support Going Concern at CV. DBU - I Nyoman Aditya Putra; M Dana Saputra; I N Sugiarta (Journal of Applied Sciences in Accounting, Finance, and Tax, 2021)
Green accounting is how to include the consequences of an event concerning the environment in financial statements. This study aims to determine whether environmental cost management at CV. DBU in Denpasar City based on green accounting. This research was conducted at the meat processing company due to their operational activities using an interpretive approach to CV. DBU. Data collection was carried out by interview technique and other secondary data support. The results of the study stated that CV. DBU based on the discussion, it was known that the implementation of green accounting has a positive impact on efforts to prevent environmental pollution. In addition, the implementation of green accounting also has an impact on increasing business sustainability. With the application of environmental accounting or green accounting the company will pay more attention to environmental problems. By paying attention to the environment, business continuity would be guaranteed.